2021
DOI: 10.3389/fclim.2021.630893
|View full text |Cite
|
Sign up to set email alerts
|

Future Prospects of Direct Air Capture Technologies: Insights From an Expert Elicitation Survey

Abstract: Direct air capture (DAC) technologies are promising but speculative. Their prospect as an affordable negative emissions option that can be deployed in large scale is particularly uncertain. Here, we report the results of an expert elicitation about the evolution of techno-economic factors characterizing DAC over time and across climate scenarios. This is the first study reporting technical experts' judgments on future costs under different scenarios, for two time periods, for two policy options, and for two di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(28 citation statements)
references
References 54 publications
(71 reference statements)
1
27
0
Order By: Relevance
“…As a result, several studies have attempted to estimate the current cost of DACS, [8][9][10][11][12][13][14] or project the cost of DACS into the future. [14][15][16][17] However, these studies all use methods inconsistent with the nature of the cost development of early-stage technologies, whose costs tend to rise during the research, development, and deployment (RD&D) phase up to the first deployed commercial scale plant, i.e., the first-of-a-kind (FOAK) plant, and then start falling as a function of deployment, as demonstrated in Figure 1. A recent method for the costing of advanced CO2 capture technologies was postulated by Rubin and co-workers.…”
Section: Introductionmentioning
confidence: 99%
“…As a result, several studies have attempted to estimate the current cost of DACS, [8][9][10][11][12][13][14] or project the cost of DACS into the future. [14][15][16][17] However, these studies all use methods inconsistent with the nature of the cost development of early-stage technologies, whose costs tend to rise during the research, development, and deployment (RD&D) phase up to the first deployed commercial scale plant, i.e., the first-of-a-kind (FOAK) plant, and then start falling as a function of deployment, as demonstrated in Figure 1. A recent method for the costing of advanced CO2 capture technologies was postulated by Rubin and co-workers.…”
Section: Introductionmentioning
confidence: 99%
“…No leakage is considered from the geological sites. 32 and decrease with learning-by-doing. Total cost of DAC is assumed, in the central projection, to start from 780$/ton CO2 removed, and the floor cost is set at 214 $/ton CO2.…”
Section: Dac As a Representative Technology For Netsmentioning
confidence: 92%
“…For example, an expert elicitation study showed that experts currently predict that the costs today lie between ~$100-2000 t-CO2 -1 falling to ~$50-1500 t-CO2 -1 by 2050 depending on future policy scenarios. 15 Furthermore, there is little to no information on the cost of DACS in locations outside the US (and perhaps Europe), and on how government policy may support the deployment and cost development of DACS projects.…”
Section: And Rinbergmentioning
confidence: 99%